Analisis Risiko Harga dan Pendapatan Usahatani Cabai Rawit di Kabupaten Kediri - Titis Surya Maha Rianti; Lia Rohmatul Maula (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Given the highly volatile commodity prices, growing cayenne pepper is a risky business. The study aims to determine the level of price and income risk of cayenne pepper farming in Kediri Regency. The research location was determined purposively, namely in Pagu Village, Pagu District, Kediri. The sampling technique was carried out by sample random sampling method with a total sample of 64 respondents. The data analysis method used to determine the level of risk is by determining the value of the coefficient of variation (CV). Based on the results of the analysis, it is known that the level of price and income risk at the research location is high with a CV value of more than 0.5. To anticipate price and income risks, farmers can use alternative combinations of inputs that minimize costs and establish a partnership system in marketing crop products. Thus farmers can do farming more safely and securely from farming risk.